The Lithuanian long-term care system - Izabela Marcinkowska (Center for Social and Economic Research (CASE), 2010)
The remarkable growth of older population has moved long-term care to the front ranks of the social policy agenda in the European Union. This paper addresses the issue of the longterm care in Lithuania, its philosophy, the legal and funding regularities, management issues and LTC policy. Its attempt is also to provide a complex set of information about the demand side of long-term care including the demographic characteristics of people in need. The paper also presents a detailed description of types of LTC available. The results confirm that the main problem of the LTC system in Lithuania is still its division between the health care system and the social system and the weak integration of these two parts of LTC services. The formal LTC system in Lithuania is still biased towards the provision of institutional care, despite the fact that a number of social projects have started in order to expand the supply of semi-stationary LTC and care provided in homes. Moreover, most care provided to the elderly and disabled is still carried out by family, neighbours, friends and volunteers. The demand for LTC, approximated by the demographic and epidemiologic structure of the population at the national and regional levels, remains high and it is expected to increase. The middle-aged population's longer average lifespan and progress in the field of medicine greatly contributes to an increasing number of disabled and older people who have difficulties in caring for themselves.
Keywords: H51; H55; I18; 330; long-term care; health care system; social services; Lithuania; Langzeitpflege; Sozialer Dienst; Gesundheitswesen; Sozialpolitik; Litauen